Academic Opportunities of Study Habits in College Students: An Instrumental Study - Remaycuna-Vasquez, Alberto; Atoche-Silva, Luz Angelica; Espinoza-Porras, Fátima Rosalía; Solano-Cavero, Jessica Karin; Pantoja-Tirado, Lucia Ruth; Seminario-Morales, María Verónica (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The evaluation of study habits as determinant factors in academic performance is a concern for educational agents because they determine the academic opportunities of students. However, a problem encountered is the accessibility of valid and reliable instruments to evaluate study habits from the students' point of view. In this sense, this paper analyzes the internal structure, reliability, and rating of the study habits perception questionnaire. The results and the practical contribution to the educational community in guiding intervention to improve students' academic opportunities are discussed.